Associations Between Social Capital and Depressive Symptoms Among College Students in 12 Countries: Results of a Cross-National Study - Backhaus, Insa; Varela, Andrea Ramirez; Khoo, Selina; Siefken, Katja; Crozier, Alyson; Begotaraj, Edvaldo; Fischer, Florian; Wiehn, Jascha; Lanning, Beth A.; Lin, Po-Hsiu; Jang, Soong-nang; Monteiro, Luciana Zaranza; et al. (Frontiers in Psychology, 2020)
Introduction: A mental health crisis has hit university campuses across the world. This study sought to determine the prevalence and social determinants of depressive symptoms among university students in twelve countries. Particular focus was placed on the association between social capital and depressive symptoms. Methods: A cross-sectional study was conducted among students at their first year at university in Europe, Asia, the Western Pacific, and Latin and North America. Data were obtained through a self-administered questionnaire, including questions on sociodemographic characteristics, depressive symptoms, and social capital. The simplified Beck’s Depression Inventory was used to measure the severity of depressive symptoms. Social capital was assessed using items drawn from the World Bank Integrated Questionnaire to Measure Social Capital. Multilevel analyses were conducted to determine the relationship between social capital and depressive symptoms, adjusting for individual covariates (e.g., perceived stress) and country-level characteristics (e.g., country income). Results: Among 4228 students, 48% of presented clinically relevant depressive symptoms. Lower levels of cognitive (OR: 1.82, 95% CI: 1.44 - 2.29) and behavioral social capital (OR: 1.51, 95% CI: 1.29 - 1.76) were significantly associated with depressive symptoms. The likelihood of having depressive symptoms was also significantly higher among those living in regions with lower levels of social capital. Conclusion: The study demonstrates that lower levels of individual and macro-level social capital contribute to clinically relevant depressive symptoms among university students. Increasing social capital may mitigate depressive symptoms in college students.